2014
DOI: 10.1002/chem.201304234
|View full text |Cite
|
Sign up to set email alerts
|

New Functional Cyclic Aminomethylphosphine Ligands for the Construction of Catalysts for Electrochemical Hydrogen Transformations

Abstract: Eight-membered cyclic functional bisphosphines, namely 1,5-di-aryl-3,7-di(2-pyridyl)-1,5-diaza-3,7-diphosphacyclooctanes (aryl=2-pyridyl, m-tolyl, p-tolyl, diphenylmethyl, benzyl, (R)-(+)-(α-methyl)benzyl), with 2-pyridyl substituents on the phosphorus atoms have been synthesized by condensation of 2-pyridylphosphine, formaldehyde, and the corresponding primary amine. The structures of some of these bisphosphines have been investigated by X-ray crystallography. The bisphosphines readily form neutral P,P-chelat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 83 publications
(128 reference statements)
2
41
0
Order By: Relevance
“…The five‐coordinate geometry of the nickel ion in 1a is not rare; five‐coordinate geometries can be divided into two categories: the trigonal bipyramid and the tetragonal pyramid . The square‐pyramidal geometry is commonly formed with pentadentate chelating ligands, or from a combination of tridentate and bidentate chelating ligands , .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The five‐coordinate geometry of the nickel ion in 1a is not rare; five‐coordinate geometries can be divided into two categories: the trigonal bipyramid and the tetragonal pyramid . The square‐pyramidal geometry is commonly formed with pentadentate chelating ligands, or from a combination of tridentate and bidentate chelating ligands , .…”
Section: Resultsmentioning
confidence: 99%
“…It appears that the nickel compounds with a benzimidazole‐based carbene ligand are more readily reduced with less negative half‐wave potentials (–1.53 V, –1.55 V) than those with the imidazole‐based carbenes (–1.66 V, –1.71 V), indicating the imidazole‐based ligands to be slightly more electron‐donating. The redox potentials of these nickel compounds with the relatively hard pyridyl ligands occur at rather negative potentials compared to Ni centers that are coordinated with softer phosphane ligands , …”
Section: Resultsmentioning
confidence: 99%
“…A binding event between the two proximal Cu centers and a single O 2 molecule was proposed to form a Cu 2 O 2 intermediate species. It was established that a proper electronic environment of the bound O 2 is important for the substrate directing the proton transport. In particular, a targeted proton transfer is required for the selective O‐O reactivity, while the specific protonation of the O 2 ‐carrying superoxo adduct bypasses the formation of peroxo‐type adducts by facilitation of the multielectron processes.…”
Section: Resultsmentioning
confidence: 99%
“…[37] Ther eduction of an O 2 speciesl igated by two proximal Cu I (phenC) sites suggested that two Cu I species were necessary for the efficient four-electron reduction of O 2 . [38] Ab inding event between the two proximal Cu centers and as ingle O 2 molecule was proposed to form aC u 2 O 2 intermediates pecies.I tw as established [40] that ap roper electronic environment of the bound O 2 is important for the sub- In the Figure 4aschematic representation of the reactions on the anode and cathode sides of the PEMFC,c atalyzed by the immobilized [Ni(P Py 2 N 3 p-Tol…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation